Lutherdom og teatralitet i Blichers »Præsten i Vejlbye« - Esmann Andersen, Claus (Danske Studier, 2014)
The article explores the significance of the religious in Steen Steensen Blicher’s short story »The Vicar of Vejlbye« (»Præsten i Vejlbye«, 1829) and, as a further perspective, in other works of Blicher. The article shows how, to my view, Walter Benjamin’s Origin of the German Mourning Play is able to throw light on the prose of Blicher. My hypothesis is that a short story like »The Vicar of Vejlbye« uses allegory and theatricality because it is weighed down by religious questions to which there are no longer any religious answers. The matrix for the plot in Blichers’ work is not the Aristotelic immanent plot of destiny but the Christian transcendent history of salvation, yet without salvation as theleological anchor. Thus, the fact that the time of Blicher was a time of religious crisis does not necessarily mean that the religious became less defining for the aesthetical. On the contrary, it is possible – on the basis of the American Benjamin-scholar Samuel Webers thoughts about theatricality as the focal point of an alternative genealogy of modernity – to see »The Vicar of Vejlbye« as one of those places where the modern in literature begins. From this point of view, the modern originates from Lutheran Christianity.